Exploring the Role of Educational City Branding in University Students’ Satisfaction: A study of Nicosia, Northern Cyprus - Dhuoki, Riman Mohammed Said Bashir; Gürdallı, Huriye (European Journal of Sustainable Development, 2025)
The research focuses on the city branding regarding educational institutions and satisfaction of university students in Nicosia, Northern Cyprus. This study provides an overview for higher educational institution authorities by evaluating the city image, urban environment and cultural heritage impact on the students. By applying quantitative approach, (100) undergraduate students that are studying in universities located in Nicosia participated in this questionnaire. Therefore, a survey evaluated satisfaction of the students via different factors of urban environment including availability of green spaces, efficiency of transportation, safety, cultural richness and housing affordability. Results show high appreciation of students in higher education institutions offerings, safety of the city and the cultural heritage. However, significant dissatisfaction was noted in areas such as housing affordability, accessibility, and public transportation. These insights highlight critical challenges in the city’s branding strategy. The study underscores the importance of aligning urban development with higher education strategies to enhance the city’s appeal. The study adds to the literature by emphasizing the relation between urban infrastructure and universities. It also recommends the integration of city branding with higher education strategies which support urban identity and enhance satisfaction of the students. Keywords: City branding; educational cities; urban environment; urban identity; students’ satisfaction; Nicosia